2008
DOI: 10.3354/meps07769
|View full text |Cite
|
Sign up to set email alerts
|

Benthic community-mediated sediment dynamics

Abstract: We assessed the influence of benthic communities on sediment properties in large defaunation experiments in replicated 16 m(2) plots on a tidal flat in the Westerschelde estuary (SW Netherlands). We compared microphytobenthos and benthic macrofauna recovery and recolonisation between control and defaunated sediments during 8 mo following the defaunation, focussing on how the temporal scale of biological responses interact with the temporal scale of sedimentological developments (grain size, bed level, erosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 61 publications
(80 reference statements)
1
63
1
1
Order By: Relevance
“…Biogeochemical processes that primarily depend on molecular diffusion of dissolved oxidants such as oxygen are expected to become established within one-two days depending on the diffusion distance and the dynamics of the microbes involved. Montserrat et al (2008) showed that benthic microalgal communities were reestablished within two weeks following anoxia for more than 6 weeks. Biogeochemical processes that depend on interface feeders and shallow bioturbators are expected to recover on time scales of weeks to months, while microbial processes that depend on particle mixing or pore-ventilation by large, deep living animals may need years to fully recover (Fig.…”
Section: Dynamics Of Faunal Response To Hypoxia and Sediment Biogeochmentioning
confidence: 99%
See 1 more Smart Citation
“…Biogeochemical processes that primarily depend on molecular diffusion of dissolved oxidants such as oxygen are expected to become established within one-two days depending on the diffusion distance and the dynamics of the microbes involved. Montserrat et al (2008) showed that benthic microalgal communities were reestablished within two weeks following anoxia for more than 6 weeks. Biogeochemical processes that depend on interface feeders and shallow bioturbators are expected to recover on time scales of weeks to months, while microbial processes that depend on particle mixing or pore-ventilation by large, deep living animals may need years to fully recover (Fig.…”
Section: Dynamics Of Faunal Response To Hypoxia and Sediment Biogeochmentioning
confidence: 99%
“…Our goals are (1) to provide a systematic and concise overview of the effect of oxygen on sediment biogeochemistry, both direct and indirect via its effect on benthic faunal communities, and (2) to explore the dynamics and response of sediment biogeochemistry both in terms of sensitivity to and resilience to (recovery from) hypoxic events. We will not cover the consequences of hypoxia on benthic primary producers because our overview is restricted to sediments not receiving sunlight (Larson and Sundbäck, 2008;Montserrat et al, 2008). Gooday et al (2009) discuss the formation, preservation and use of proxies in hypoxia research and cover in detail the effect of hypoxia on trace element sediment geochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…This might explain the lack of response of the communities in terms of densities, species richness, and especially biomass in our study, particularly in the eastern part although oxygen conditions did significantly improve there. The process that took at least much more than half a year in the experiment described by Montserrat et al (2008) and Van Colen et al (2008) might take at least more than 3.5 years in our case as recolonization in the much larger defaunated areas of Lake Veere is probably more dependent of larval recruitment instead of adult settlement. This is in line with the recordings of Beukema et al (1999) who found no complete recovery of the biomass within 4 years after anoxia in the Wadden Sea at, compared to the current study, relatively small patches with good opportunities for recolonization from the surroundings.…”
Section: Effects Of the Restoration Measure On The Macrozoobenthic Comentioning
confidence: 99%
“…Also the physical or chemical constitution of the environment can play a role in whether or not there is successful settlement. Montserrat et al (2008) and Van Colen et al (2008) showed that a plot that was artificially defaunated by asphyxia showed a different composition of the sediment in terms of cohesiveness and sediment strength due to the lack of bioturbation and biodiffusion. The communities went through a series of succession states starting with a microphytobenthic community to a community of tube builders before gradually surface disruptors and pelletizers returned.…”
Section: Effects Of the Restoration Measure On The Macrozoobenthic Comentioning
confidence: 99%
“…4). Synergistic and antagonistic effects caused by interactions among species may render both scenarios of this conceptual model invalid Orvain et al, 2007;Montserrat et al 2008). The true outcome will most likely be intermediate and unpredictably dictated not only by species-specific effects, but also by their interactions as well as environmental and sediment conditions.…”
Section: à2mentioning
confidence: 99%